2014
DOI: 10.1007/s12192-013-0434-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipotropes promote immunobiochemical plasticity and protect fish against low-dose pesticide-induced oxidative stress

Abstract: An experiment was conducted to evaluate the role of different lipotropes in modulating immunity and biochemical plasticity under conditions of sublethal low-dose pesticide-induced stress in fish. Labeo rohita fish fingerlings were divided in two sets with one set of fish continuously exposed to low-dose endosulfan (1/10th of 96-h LC 50 ) for 21 days, the other was unexposed, and both sets of fish were fed with practical diets supplemented with either 2 % lecithin, 0.5 % betaine, or 0.1 % choline and compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 94 publications
4
15
0
Order By: Relevance
“…The neurotransmitter, acetylcholine hydrolysing into choline and acetic acid and responsibility of this phenomenon fully depend on acetylcholine esterase. It is one of the most important indices in toxicity studies because it catalyses hydrolysis of acetylcholine at the synaptic junctions, thereby facilitating the nerve impulse transmission from one cholinergic neuron to the others [49]. In the present study, the brain AChE activity in C. chanos exposed to endosulfan was inhibited, suggesting similar disrupting cholinergic neurotransmission through inhibition of AChE [35].…”
Section: Discussionsupporting
confidence: 47%
“…The neurotransmitter, acetylcholine hydrolysing into choline and acetic acid and responsibility of this phenomenon fully depend on acetylcholine esterase. It is one of the most important indices in toxicity studies because it catalyses hydrolysis of acetylcholine at the synaptic junctions, thereby facilitating the nerve impulse transmission from one cholinergic neuron to the others [49]. In the present study, the brain AChE activity in C. chanos exposed to endosulfan was inhibited, suggesting similar disrupting cholinergic neurotransmission through inhibition of AChE [35].…”
Section: Discussionsupporting
confidence: 47%
“…hypophthalmus have been significantly improved with Zn supplementation might be due to stimulates cholinergic activity in certain brain regions which may play a role in the therapeutic effect of Zn micronutrient to improved AChE activities. Similar results were found in case of lecithin (Kumar, Jadhao, Chandan, Akhlak & Rana, ; Kumar, Jadhao, Chandan & Rana, ; Muthappa et al., ) and pyridoxine (Kumar, Ambasankar, Krishnani, Bhushan, et al., ) fed to Labeo rohita and Chanos chanos respectively. In our earlier study, lecithin and pyridoxine were responsible for enhancement of thermal tolerance in C. chanos and also take important role in improvement of acetyl cholinesterase activities during end of the LTmin and LTmax (Kumar, Ambasankar, Krishnani, Kumar, et al., ; Kumar et al., ; Kumar, Minhas, et al., ).…”
Section: Resultssupporting
confidence: 77%
“…Our previous study (Kumar et al, 2011b) found reduction in brain AChE activity in Oreochromis mossambicus when exposed to endosulfan for 96 h and also Kumar et al, 2012 reported that supplementation of lecithin in the diet of L. rohita resulted in higher AChE activity. To corroborate our finding Muthappa et al (2013) reported that exposure to endosulfan resulted in a significant reduction in AChE activity in L. rohita and supplementation of lecithin resulted in significantly higher AChE activity. Gupta et al (2014) reported that levan supplementation in the diet improved AChE activities in common carp exposed to fipronil.…”
Section: Acetylcholine Esterase (Ache) Activitysupporting
confidence: 88%